DETEKSIPOLAMAKANANKHASKULONPROGO “GEBLEK” DENGAN IMAGES BLENDINGDAN OPERATOR CANNY - Putri Taqwa Prasetyaningrum (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2016)
The snack is traditional food made from tapioca flour with fried onions savory seasoning. The round shape is colored white and processed with the way fried. These foods are popular as snacks typical of the area of Kulon progo Regency. Image is the image on a two-dimensional field. In mathematical reviews. The image is a continuous function of light intensity in two dimensions. In computers, a digital image is saved as a file with a specific format. The image shows how to format a digital image is stored, for example, whether with a compression or not. Examples of digital image formats are .bmp, .jpg, .PNG, .tif, and so on. Digital image size expressed in pixels (picture elements). This description describes the merging of two different images into an image in the form of new patterns. This process of merging using matlab with images blending, then from the results of the merge image searchable form of the pattern using the Canny operator. The size of the original image i.e. image of flowers and circles must be the same image that is 400 x 300 pixels in jpg format. The results obtained in the form of a composite image of two images in the shape of a new image of the pattern that is the pattern image to resemble floral patterns.digital imagery